DAUN SIRIH DALAM KARYA SENI GRAFIS - Mido Putra, Drs, Irwan, M.Sn., Yofita sandra, S.Pd., M.Pd. (Universitas Negeri Padang, 2017)
Creation of this finally project aims for how to visualize phenomena the use of betel leaf associated with Minangkabau culture shift. Betel leaf is closely related to the philosophy tradition that Betel leaf is the symbols of Inviting, receiving guests and other customary rituals.The methods and processes that used in the creation of this graphic art through several stages: a) preparation, b) Elaboration c) Synthesis d) Realization the e) FinishingFrom this graphic arts can be concluded that the betel leaf is a media of social communication in Minangkabau culture and inherited from ancestors.due to the ancestral era to the more sophisticated field, the write try to remember the using of betel leaves which slowly abandoned.Keywords: Betel Leaves, Graphic Art, serigraphy